Journal Of Indonesia Economy & Bisnis = Jurnal Ekonomi & Bisnis Indonesia - Suad Husnan (Faculty of Economic & Business Universitas Gadjah Mada, 2014)
No. Penulis --- Judul Artikel --- Halamanrn1. Woro Dwi Suryani and Sumiyana --- Task-Technology Fit and Person-Job Fit : A Beauty Contest to Improve The Success of Information Systems --- 99-117rn2. Hirwan Hamidi --- The Impact on Farm Profits of a Company?s Partnership With a Potato Farm (The Case of the Partnership Between PT. Indofood Fritolay Makmur and Potato Famers in Sembalun District, in the Province of West Nusa Tenggara) --- 118-128rn3. Suad Husnan, Mamduh M. Hanafi and Muhammad Munandar --- Price Stabilization and IPO Underpricing : An Empirical Study in the Indonesian Stock Exchange ---- 129-141rn4. Irwan Taufiq Ritonga ---- Developing a Measure of Local Government?s Financial Condition ---- 142-164rn5. Sahid Susilo Nugroho, Rokhima Rostiani and Indriyo Gitosudarmo --- The Impacts of Country-of-Origin, Product Involvement, and Product Familiarity on Product Evaluation --- 165-182rn6. Rokhima Rostiani, Widya Paramitha, Handini Audita, Risa Virgosita, Teguh Budiarto and Boyke R. Purnomo --- Understanding Social Enterprises in Indonesia : Drivers and Challenges ---- 183-191rn7. Sudiyanti ---- Book Review : Business Sustainability : Essentials for Business ---- 192-194